Beyond Instrumentalised Politics : Re-Conceptualising Public Governance - Thomson, Garrett; Gill, Scherto (2024)
Political thinking tends to outline reforms to existing political institutions. In contrast, Beyond Instrumentalised Politics argues for the need for systemic transformation. It articulates the evaluative principles for good governance, and employs these principles to argue for a new political system. Because persons are non-instrumentally valuable, good governance requires that all people are respected equally, and this necessitates a participatory democracy. The book investigates how such a democracy might function through consensus-based decision-making and argues for a redefinition of consensus. It characterises the local and national institutions required for public governance thus conceived. This includes the creation of various types of spaces for deep dialogue and mutual inquiry. This book demonstrates how this innovative vision would transform our current conceptions of governance.